New species of the genus Dolophilodes Ulmer 1909 (Trichoptera: Philopotamidae) from Singalila National Park, West Bengal, India - Pandher, Manpreet Singh; Kaur, Simarjit; Parey, Sajad H. (Zootaxa, 2023)
This paper is another contribution to knowledge of the caddisfly fauna of India. Here we describe and illustrate three new species of Dolophilodes Ulmer 1909: D. dhritiae sp. nov., D. similis sp. nov., and D. laminata sp. nov. all from Singalila National Park, West Bengal. With these additions, genus Dolophilodes is now represented by 9 species from India.